Pengaruh Stres Kerja Dan Beban Kerja Terhadap Disiplin Kerja Pegawai Puskesmas Wawo Kabupaten Bima - Muhammad Kurais Anwar; Muhammad Yusuf (Universitas Kristen Indonesia Toraja, 2023)
Community Health Centers are functional organizational units that carry out comprehensive, integrated, equitable health efforts that are acceptable and affordable to the community with the active participation of the community and using the results of the development of appropriate science and technology, at a cost that can be borne by the government and the wider community. in order to achieve optimal health status, without neglecting the quality of service to individuals and the community.